Cross-sectional study of effect of adiposity and hypertensive states on airway dynamics - Gautam, Kunal Kishor; Saxena, Deepak; Kanchan, Arvind; Ahmad, Nisar; Saini, Rahul; Mujeeb, Naushi (International Journal of Research in Medical Sciences, 2019)
Background: Adiposity and hypertensive states are major burden for community. It causes many health-related issues, including problems related to respiratory system. It is proposed that pulmonary functions can be affected in obese hypertensive and obese normotensive adults compared to non-obese normotensive adults. The objective of the study was to find out the effect of adiposity and hypertensive states on the airway dynamics. Methods: About 30 male obese normotensives and 30 male obese hypertensive subjects were selected as study participants. 30 age-controlled non-obese, normotensive males were selected as controls. All participants were in the age group of 40 to 60 years. The pulmonary functions measured were FVC, FEV1, FEV1% and PEFR. All the participants performed 3 attempts of spirometry and maximum among the three recordings were used for analysis. ANOVA followed by Post hoc analysis to find out any significant differences between these groups. Spearman’s rank correlation was used. Results: There was a statistically significant differences in BMI between the group I and group II and III. There was a significant difference in SBP and DBP between obese normotensive (group II) and obese hypertensive (group III) subjects. There were significant decline in % predicted values of PFT parameters, on comparing obese normotensive and obese hypertensive when compared to non-obese normotensive participants. There were statistically significant negative correlations between age and FEV1 as well as BMI and PEFR. Conclusions: There was a significant decrease the pulmonary functions in obese normotensive and obese hypertensive adults in comparison to non-obese normotensive adults. It can be concluded that body weight and adiposity as well as high blood pressure creates deleterious effect on airway dynamics.